1994
DOI: 10.1111/j.1540-4560.1994.tb02421.x
|View full text |Cite
|
Sign up to set email alerts
|

Balancing Personal Needs with Environmental Preservation: Identifying the Values that Guide Decisions in Ecological Dilemmas

Abstract: A taxonomy of values that specifies three domains (i.e., economic, social, and universal) was developed and used to explore the influence personal values have on people's decisions when placed in ecological dilemmas. Hypothetical scenarios, which pitted economic need against environmental preservation, were used to elicit individual decisions. The influence of economic and social conditions was also experimentally tested. Results from 144 University students show that subjects who embrace a universal value ori… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
75
0
3

Year Published

1999
1999
2015
2015

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 131 publications
(83 citation statements)
references
References 13 publications
1
75
0
3
Order By: Relevance
“…Studies in which the role of moral norms in environmental behaviors has been investigated have consistently found that people endorsing moral values are more inclined to express such values through active behaviors, rather than through inaction (e.g., Black, Stern, & Elworth, 1985;Cialdini, Reno, & Kallgren, 1990;Hopper & Nielsen, 1991;Stern, Dietz, & Kalof, 1993). People with such value orientations are more willing to pursue environmental protection in the face of negative economic or social outcomes (Axelrod, 1994). They may be driven (at least partially) by nonconsequentialist (deontological) principles (their rationale for action is that it is "the right thing to do").…”
mentioning
confidence: 99%
“…Studies in which the role of moral norms in environmental behaviors has been investigated have consistently found that people endorsing moral values are more inclined to express such values through active behaviors, rather than through inaction (e.g., Black, Stern, & Elworth, 1985;Cialdini, Reno, & Kallgren, 1990;Hopper & Nielsen, 1991;Stern, Dietz, & Kalof, 1993). People with such value orientations are more willing to pursue environmental protection in the face of negative economic or social outcomes (Axelrod, 1994). They may be driven (at least partially) by nonconsequentialist (deontological) principles (their rationale for action is that it is "the right thing to do").…”
mentioning
confidence: 99%
“…What this suggests is that one's environmental value could make him or her go for green building. However, the result of this move could have weak or fair relationship as they could be presumably mediated by some economic, social and environmental variables [24,25,26,27].…”
Section: Quest For Enhancement and Protection Of Eco-system And Bio-dmentioning
confidence: 99%
“…The relationship could reduce if ecological behaviour instead of ecological behaviour intention is considered [27,21]. Theorists acknowledge that one's environmental values are related to ecological behaviour intention and could be mediated by other environmental behavioural intentions [24,25,29].…”
Section: Quest For Minimization Of Site Impactmentioning
confidence: 99%
“…Possible consequences of this would be malnutrition and mental health issues, including the emergence of feelings of unhapiness, exclusion, and marginalization. As seen in many places, the 'weak and unhappy' social sub-system could easily generate governability problems in the long-run (Axelrod 1994;Blount and Pitchon, 2007). On the contrary, tourism has only slightly been recognized as an "indirect" driver (Dirección Parque Nacional Galápagos DPNG 2014) for the effects on Galapagos environment, which disregards the real effect of this industry on the islands sustainability.…”
Section: Features Influencing Gmr Governabilitymentioning
confidence: 99%